P‐1: World's First 85‐in. 8K4K 120Hz 1G1D LCD with Oxide TFT Using Four‐Mask Array Process. Issue 1 (28th June 2021) - Ge, Shi-Min; Li, Shan; Hu, Xiao-Bin; Gong, Cheng; Zhao, Wen-Da; Li, Yu-Zhi; Zheng, Ze-Ke; Dai, Chu-Hong; Liu, Quan-Sheng; Lei, Xing; Guo, Li; Fu, Xin-Bo; et al.
Abstract : We successively fabricated 1G1D 85″ 8K4K 120Hz LCD with oxide TFT using only four‐mask array process. The transmittance and contrast ratio of our 85″ panel are 4.5% and 5000, which show 8% and 15% improvement than a‐Si TFT counterparts. The power consumption is reduced 20% compared to a‐Si TFT panels.